TCP-UEM : uma abordagem para controle de congestionamento sensível a falhas em enlaces sem fio - Gonçalves, Renato Fernando Silva (2018)
The emergence of computer networks has provided great advances in computing. The high cost of a computational resource at that time was one of the major responsible for popularizing computer networks. Expensive resources and data could be shared. Computer networks have become a no-return road. The union of these networks made possible the creation of the Internet. New technologies and protocols were developed. Access to the Internet can be done virtually anywhere in the world thanks to the evolution of networks and mobility technology. However, to use this technology, which evolved solidly on the wired Internet, in wireless networks is a major challenge. There is a huge difference between wired networks and wireless networks. Wireless Networks do not have predictability, using air as a means of physical access. Wireless networks are subject to a high rate of transmission errors, frequent disconnections due to handoffs, unexpected obstacles that attenuate the quality signal and others. The Internet has helped to popularize and standardize several technologies, such as the TCP / IP. The TCP protocol is transport layer protocol more used by applications on Internet, but it has evolved to work in a stable link, without much variation. Thus, TCP is inefficient when used in wireless networks, because TCP understands as a sign of congestion packets losses faced by wireless networks, causing the control algorithm of TCP to be activated erroneously causing degradation of the efficiency of the protocol. Several efforts have been made to improve the efficiency of communications on a link that uses air as the physical environment. Some solutions try to treat the problem at the transport layer. Others seek assistance from the link layer. There are also the solutions which propose the creation of a new protocol, redesigned exclusively for wireless environments. In fact, there is a consensus about the weaknesses faced by TCP when used in wireless networks, as well as which features a protocol must have to be effective. Facing such a scenary, this work compares some of the existing solutions and presents a new variant of TCP-UEM whose purpose is to detect link failures while keeping its end-to-end semantics, ie, without relying on the help of other layers to perform this detection,